Analysis of Graduate Success Patterns Based on Association Rule Mining to Increase the Achievement of the Performance Index of Higher Education Graduates - wasilah, wasilah; Halimah, Halimah (International Journal of Artificial Intelligence Research, 2023)
The main performance index (KPI) of graduates is an important factor for universities. However, there is still very little research that discusses the achievement of IKU graduates. If this is managed well, universities can take more effective action to improve the quality of education and prepare graduates to be successful in their careers. This research will utilize data mining to photograph the achievements of implementing one of the main performance indices in higher education.